THE IMPORTANCE OF ENDOTHELIAL DYSFUNCTION IN THE DEVELOPMENT OF DISORDERS OF THE HEMOSTASIS SYSTEM IN PATIENTS WITH RHEUMATOID ARTHRITIS (Proceedings of International Educators Conference, 2024)
The literature review presents current data on the physiology and pathology of the endothelium. It has been noted that endothelial dysfunction is the main pathogenetic mechanism in the development of many diseases, and a more in-depth study of the morphofunctional structure of the vascular endothelium in various pathologies can contribute to early diagnosis and prevention.